Baicalein Exerts Neuroprotective Effects in FeCl3-Induced Posttraumatic Epileptic Seizures via Suppressing Ferroptosis - Qin Li; Qin Li; Qin Li; Qin Li; Qiu-Qi Li; Qiu-Qi Li; Qiu-Qi Li; Qiu-Qi Li; Ji-Ning Jia; Ji-Ning Jia; Ji-Ning Jia; Ji-Ning Jia; et al. (Frontiers Media S.A., 2019)
Posttraumatic epilepsy (PTE) is a prevalent type of acquired epilepsy secondary to traumatic brain injury, and is characterized by repeated seizures. Traditional antiepileptic drugs have minimal response in preventing posttraumatic epileptic seizures. It is essential for the development of new therapeutic strategy. Our previous work disclosed a potent neuroprotective role of baicalein, a flavonoid extracted from Scutellaria baicalensis Georgi, against inherited epilepsy in rats. Whether baicalein has protective potential in posttraumatic epileptic seizures and the possible molecular mechanism remain elusive. Additionally, the brain is vulnerable to lipid peroxidation-induced damage due to high consumption of oxygen and abundant polyunsaturated fatty acids in neuronal membranes. Our present investigation aimed to elucidate whether baicalein exerts neuroprotective effects on posttraumatic epileptic seizures by inhibiting ferroptosis, a newly discovered lipid peroxidation-dependent cell death modality. We found that baicalein significantly reduced seizure score, number of seizures, and average seizure duration in an iron chloride (FeCl3)-induced PTE mouse model. The neuroprotective effect of baicalein was also validated in a ferric ammonium citrate (FAC)-induced HT22 hippocampal neuron damage model. Moreover, in vitro, baicalein could remarkably decrease ferroptotic indices (lipid reactive oxygen species, 4-hydroxynonenal, and prostaglandin endoperoxide synthase 2) and inhibit the expression of 12/15-lipoxygenase (12/15-LOX) in an iron-induced HT22 cell damage model. These findings were also validated in a mouse PTE model. It was concluded that baicalein exerted neuroprotective effects against posttraumatic epileptic seizures via suppressing ferroptosis and 12/15-LOX was likely to be involved in baicalein's neuroprotection.